2015
DOI: 10.1371/journal.pone.0133959
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Brain Network Coupling Predicts Total Sleep Deprivation Effects on Cognitive Capacity

Abstract: Interactions between large-scale brain networks have received most attention in the study of cognitive dysfunction of human brain. In this paper, we aimed to test the hypothesis that the coupling strength of large-scale brain networks will reflect the pressure for sleep and will predict cognitive performance, referred to as sleep pressure index (SPI). Fourteen healthy subjects underwent this within-subject functional magnetic resonance imaging (fMRI) study during rested wakefulness (RW) and after 36 h of total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…Its magnitude remained strong, even after we controlled for relevant covariates (i.e., age, sex, TIV) and type I errors. Interestingly, we also found that these identified global regions are components of large-scale brain networks categorized by a large body of functional magnetic resonance imaging (fMRI) studies with adult study populations in clinical settings and nonclinical settings 32,[35][36][37][38][39][40][41][42][43] . The networks include the default mode network (DMN), central executive network (CEN), visual network (VN), somatosensory network (SSN), and salience network (SN).…”
Section: Discussionmentioning
confidence: 99%
“…Its magnitude remained strong, even after we controlled for relevant covariates (i.e., age, sex, TIV) and type I errors. Interestingly, we also found that these identified global regions are components of large-scale brain networks categorized by a large body of functional magnetic resonance imaging (fMRI) studies with adult study populations in clinical settings and nonclinical settings 32,[35][36][37][38][39][40][41][42][43] . The networks include the default mode network (DMN), central executive network (CEN), visual network (VN), somatosensory network (SSN), and salience network (SN).…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased connectivity between the hippocampus, the thalamus and the DMN predicts higher subjective sleepiness and is associated with worse working-memory performance under sleep-loss conditions 34,35 . By contrast, increased connectivity between the thalamus and the precuneus under SD conditions predicts greater recovery of working-memory performance, relative to the sleep-rested state.…”
Section: Attention and Working Memorymentioning
confidence: 99%
“…Moreover, sleep deprivation has been shown to have a detrimental effect on certain aspects of working memory, such as filtering efficiency, whilst Stroop test scores show degradation; however, this has been evidenced to be due to deficits in reaction time rather than processing skills [5,[11][12][13][14][15][16][17]. Taken together, these data suggest that sleep deprivation may have a limited effect on cognitive ability in university students.…”
mentioning
confidence: 99%